THE SECOND-ORDER PROPERTY VIEW OF EXISTENCE. - KATZAV, JOEL (Pacific Philosophical Quarterly, 2008)
In this paper, I examine the current case against the second-order property view of existence through a discussion of Colin McGinn's up to date statement of this case. I conclude that the second-order property view of existence remains viable.